The efficiency of executing technical actions by female volleyball players depending on their positions on the court - Cieminski, C. (Baltic Journal of Health and Physical Activity, 2017)
Background: The aim of the study was to determine differences in the efficiency of executing technical actions by female volleyball players taking into account their positions on the court. Material/Methods: The research material comprised results of the efficiency of female volleyball players` technical actions (n = 98) participating in the 2015 Women`s European Volleyball Championship. The subjects were divided into five groups: receivers, middle blockers, spikers, setters, and liberoes. The following technical actions were analysed: attack, block, serve, and receiving a serve. In order to determine the differences between the studied groups, statistical tests were used. The Scheffe test was used to compare the efficiency in attack, block, and serve. Student`s T-test was used to compare receiving the serve. Results: Middle blockers are more efficient in attack than spikers by 6.82% (p < 0.05) and receivers by 9.61% (p < 0.001). Middle blockers also gain more points in the block per set than receivers (delta x = 0.39, p < 0.001), setters (delta x = 0.49, p < 0.001) and spikers (delta x = 0.35, p < 0.01). Liberoes present the efficiency in receiving the serve higher by 6.07% (p < 0.05) than receivers. Conclusions: Efficiency in attack, block and receiving a serve significantly diversifies players at differentpositions. Their positions on the court do not affect the efficiency of the serve. These differences may arise from the game tactics of the teams and may be related to different tasks realised at particular positions.